Evaluación de la calidad microbiológica del agua del casco urbano de Guaranda mediante técnicas de cultivo, caracterización por perfiles bioquímicos y pruebas moleculares (PCR) - Taco Amangandi, Nataly Mishelle (2025)
The present research project Evaluation of the microbiological quality of the water in the urban area of Guaranda using culture techniques, characterization by biochemical profiles and molecular PCR tests, aims to evaluate the microbiological quality of drinking water in Guaranda by identifying pathogenic microorganisms through culture techniques, biochemical profiles and molecular analysis (PCR) in order to guarantee the safety of the water resource. For them, 50 georeferenced water samples were analyzed randomly following the guidelines of the NTE INEN 2169: 2013 (conservation and transport), NTE INEN 2176: 2013 (sampling techniques) and INEN 2176: 1998 standards, thus using two main methodologies for water analysis: Culture technique where Compact Dry boxes were used for the rapid detection of total and fecal coliforms, following the protocols of ISO 9308-1: 2014, as well as specific culture media (selective agar) for the identification of Escherichia coli, Salmonella spp and Listeria monocytogenes, validated under ISO 11133 regulations. Molecular techniques (PCR) in this methodology after the purification of microorganisms through selective cultures and biochemical tests (including IMViC), DNA amplification was carried out using primers specific (Invitrogen) to detect Escherichia coli, Salmonella spp and Listeria monocytogenes, (including serotype OH157:H7). As controls, Certified Batteries provided by the research department were used. Escherichia coli 2% (1/50), Salmonella spp 2% (1/50) and Listeria monocytogenes 9% (5/50) were detected; this result was confirmed by gel electrophoresis. In conclusion, the presence of these pathogens in drinking water represents a health risk, which requires the implementation of monitoring and control measures in distribution networks.